Community Leaders' Perceptions of Urban Forests in Hillsborough County, Florida - Francisco Escobedo; Jennifer A. Seitz; Robert J. Northrop; Molly K. Moon (EDIS, 2008)
Revised! FOR-194, a 2-page fact sheet by Francisco Escobedo, Jennifer A. Seitz, Rob J. Northrop, and Molly K. Moon, compares the results from a needs assessment in Hillsborough County to a national urban tree survey and shares some initial insights into the Gulf Coast community’s perceptions and beliefs regarding urban trees. Includes references. Published by the UF School of Forest Resources and Conservation, July 2008.